Differences in the Healing of Perineal Wounds in Postpartum Mothers and Hecting Using the Dotted Technique and the Basting Technique - Mesrida Simarmata (Institute of Computer Science (IOCS), 2022)
Many factors influence the healing of perineal wounds such as internal, external to the mother and factors from health workers. Healing efforts can be carried out by non-pharmacological methods, namely Kegel exercises, mobilization, herbal concoctions. Healing perineal wounds from the perspective of health workers such as suturing techniques. There are several techniques for sewing perineal wounds, such as interrupted, continuous, subticular. The purpose of this study was to see differences in the healing of perineal wounds in postpartum mothers using the interrupted technique and the subticular technique at the T and BPM D Clinics in Deli Serdang Regency in 2020. The design of this study was an experiment with a longitudinal time approach. Sample: All postpartum women who experienced perineal injuries at the Second Grade clinic at T and BPM D Clinics were 20 people. Results: The average perineal wound healing using the basting technique was faster healing (15.20) than the dotted technique (17.40) . The results of the bivariate analysis stated that there was no significant difference between the healing time of the perineal hecting wound with the dotted technique and basting with a value of p = 0.271 (> 0.005). Health workers should improve their ability to handle episiotomy wounds so that they heal quickly and do not get infected